Navigational methods in 3D virtual environments - Fu, Zi Xiang (2019)
3D virtual environments are created to simulate 3D space in computers. They are created for many uses, such as gaming and virtual reality. There are various game engines that can create such environment. Objects will also be created to interact and move in the environment. Pathfinding in this context refers to the ways the object can get from current location to desired location.